Sustained Response and Rationale of Programmed Cell Death-1-Targeting for Progressive Multifocal Leukoencephalopathy. (30th September 2019) - Audemard-Verger, Alexandra; Gasnault, Jacques; Faisant, Maxime; Besse, Marie-Catherine; Martin-Silva, Nicolas; Berra, Mado; Fournier, Luc; Boutemy, Jonathan; Maigne, Gwenola; De Boysson, Hubert; Ruet, Alexis; Vabret, Astrid; et al.
Abstract: In this study, we report a complete (clinical, radiological, and virological) sustained (1 year) response after nivolumab salvage therapy in a progressive multifocal leukoencephalopathy patient. Analyses of the cells infiltrate in a pretreatment brain biopsy suggest that parenchymal programmed cell death-L1 + macrophages could be the T-cells partnership in immune exhaustion and virus escape. Abstract : PD-1 and its ligand are pivotal in the T-cell-exhaustion pathway involved in viral infections. In this paper, we report a complete response after nivolumab salvage therapy in a progressive multifocal leukoencephalopathy patient. Analyses of brain biopsy suggest that PD-L1+ macrophages could be the T-cells partnership in immune exhaustion and virus escape.